Improving of Vibration Resistance of Boring Tools by Big Diameter Holes Tooling on Lathe. (2016) - Khoroshailo, Vadim; Kovalov, Viktor; Dašić, Predrag
Abstract: This paper presents a mathematical model of vibratory displacement of the toll point under the action of variable forces with regard to the application of the developed tooling system. A three-dimensional model was also created, on the base of which the design of the tooling system was developed. As a result graphs of vibratory displacement of the toll point were obtained, which allow us to judge about the decrease of vibration amplitude in the cutting process. The conducted experimental studies have shown the increased vibration resistance of boring tools when using the developed tooling system. Decreasing of the vibration amplitude by cutting process can improve the quality of the machined surface.